β3-adrenergic-receptor allele distributions in children, adolescents and young adults with obesity, underweight or anorexia nervosa - Hinney, Anke; Lentes, K.-U.; Rosenkranz, K.; Barth, N.; Roth, H.; Ziegler, A.; Hennighausen, K.; Coners, H.; Wurmser, H.; Jacob, K.; Römer, G.; Winnikes, U.; et al. (International journal of obesity, 1997)
OBJECTIVE: The missense mutation (64Trp to 64Arg) in the Β3-adrenergic-receptor has previously been described to confer a genetic predisposition to the development of obesity. DESIGN: To test the hypothesis we evaluated allele frequencies in children, adolescents and young adults who belonged to different weight groups that were delineated with percentiles for the body mass index (BMI; kg/m2). SUBJECTS: 99 underweight probands (BMI ≤15th percentile). 80 normal weight probands (BMI: 5th-85th percentile). 238 obese children and adolescents (BMI ≥97th percentile). 84 patients with anorexia nervosa (AN). MEASUREMENTS: The cohorts were screened by polymerase chain reaction with subsequent restriction fragment length polymorphism (PCR-RFLP) analysis. Data were statistically analysed for association. In addition to these case control studies, the transmission disequilibrium test (TDT) was applied to 80 families of obese probands and to 52 families of patients with AN. RESULTS: Both the tests for association and linkage were negative. The Trp64Arg allele frequencies in the three weight groups (obesity: 0.071; normal weight: 0.081; underweight: 0.056) and the AN patients (0.054) were similar. Extremely obese individuals showed no excess of the Trp64Arg allele. No homozygotes for the Trp64Arg allele were detected. CONCLUSION: Heterozygosity for the Trp64Arg allele is not of major importance in regulation of body weight in individuals younger than 35 y. Additionally, the extreme obese subgroup is not enriched for the polymorphism.